2020
DOI: 10.1051/0004-6361/201935756
|View full text |Cite
|
Sign up to set email alerts
|

Localizing the γ-ray emitting region in the blazar TXS 2013+370

Abstract: Aims. The γ-ray production mechanism and its localization in blazars are still a matter of debate. The main goal of this paper is to constrain the location of the high-energy emission in the blazar TXS 2013+370 and to study the physical and geometrical properties of the inner jet region on sub-pc scales. Methods. TXS 2013+370 was monitored during 2002-2013 with VLBI at 15, 22, 43, and 86 GHz, which allowed us to image the jet base with an angular resolution of ≥ 0.4 pc. By employing CLEAN imaging and Gaussian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 100 publications
2
8
0
Order By: Relevance
“…In the LERG Centaurus A (Müller et al 2011), the jet was observed to be freely expanding already on scales of ∼0.1 pc, or ∼10 4 R S for M BH = 5 × 10 7 M (Neumayer 2010), in agreement with our findings for NGC 315 and other LERG. On the other hand, studies of the jet shape in some high redshift FSRQs (Algaba et al 2019;Traianou et al 2020) locate the shape transition at distances >10 6 R S , as found for the HEG in our sample.…”
Section: Transition Distancesupporting
confidence: 72%
See 1 more Smart Citation
“…In the LERG Centaurus A (Müller et al 2011), the jet was observed to be freely expanding already on scales of ∼0.1 pc, or ∼10 4 R S for M BH = 5 × 10 7 M (Neumayer 2010), in agreement with our findings for NGC 315 and other LERG. On the other hand, studies of the jet shape in some high redshift FSRQs (Algaba et al 2019;Traianou et al 2020) locate the shape transition at distances >10 6 R S , as found for the HEG in our sample.…”
Section: Transition Distancesupporting
confidence: 72%
“…Several observational studies have been performed with the aim of determining the extension of the acceleration and collimation region, thus providing constraints for theoretical models. Such studies were mostly focused on the analysis of low-luminosity radio galaxies, such as NGC 6251 (Tseng et al 2016), 3C 84 (Giovannini et al 2018), 3C 270 (Nakahara et al 2018), 3C 264 (Boccardi et al 2019), NGC 1052 (Nakahara et al 2020) and M 87 (Asada & Nakamura 2012;Mertens et al 2016;Hada et al 2016;Kim et al 2018;Nokhrina et al 2019), but some constraints for high-luminosity radio galaxies, like Cygnus A (Boccardi et al 2016a,b;Nakahara et al 2019), and blazars (Giroletti et al 2008;Akiyama et al 2018;Hada et al 2018;Algaba et al 2019;Traianou et al 2020) were also provided. Moreover, part of the MOJAVE sample was investigated by Pushkarev et al (2017), Kovalev et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the LERG Centaurus A (Müller et al 2011), the jet was observed to be freely expanding already on scales of ∼0.1 pc, or ∼10 4 R S for M BH = 5 × 10 7 M (Neumayer 2010), in agreement with our findings for NGC 315 and other LERG. On the other hand, studies of the jet shape in some high redshift FSRQs (Algaba et al 2019;Traianou et al 2020) locate the shape transition at distances > 10 6 R S , as found for the HEGs in our sample.…”
Section: Transition Distancesupporting
confidence: 77%
“…Several observational studies have been performed with the aim of determining the extension of the acceleration and collimation region, thus providing constraints for theoretical models. Such studies were mostly focused on the analysis of lowluminosity radio galaxies, such as NGC 6251 (Tseng et al 2016), 3C 84 (Giovannini et al 2018), 3C 270 (Nakahara et al 2018), 3C 264 (Boccardi et al 2019), NGC 1052 (Nakahara et al 2020) and M 87 (Asada & Nakamura 2012;Mertens et al 2016;Hada et al 2016;Kim et al 2018;Nokhrina et al 2019), but some constraints for high-luminosity radio galaxies, like Cygnus A (Boccardi et al 2016b,a;Nakahara et al 2019), and blazars (Giroletti et al 2008;Akiyama et al 2018;Hada et al 2018;Algaba et al 2019;Traianou et al 2020) were also provided. Moreover, part of the MOJAVE sample was investigated by Pushkarev et al (2017); Kovalev et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small redshift cut, the sample in Boccardi et al (2021) did not include any Flat Spectrum Radio Quasars (FSRQ), forming the parent population of HERG in the unified scheme. However, some first results for this class of sources have been obtained: in TXS 2013 + 370 (Traianou et al 2020) and 4C 38.41 (Algaba et al 2019) a shape transition was detected at a distance 106RnormalS through the analysis of cm‐ and mm‐VLBI data. The third new source included in Figure 2 is the LERG Centaurus A.…”
Section: The Extent Of the Collimation Zone In Heg And Legmentioning
confidence: 99%